PENGOLAHAN SAMPAH MELALUI KOMPOSTER DAN BIOPORI DI DESA SEDAPURKLAGEN BENJENG GRESIK - Anak Agung Sagung Alit Widyastuty; Abdul Haqqi Adnan; Nurul Arijah Atrabina (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
Waste is a problem that must be faced by residential communities both in urban and rural settlements, so it needs to be systematically structured and sustainable. Conventional waste handling that has been implemented by the community cannot produce an appropriate solution, this is evident that there is still a large volume of waste that has not been managed properly. The purpose of implementing community service activities in the village of Sedapurklagen in Benjeng Gresik is to utilize household waste through compoter and biopori as well as the application of Biopori to treat household waste that can also reduce waterlogging during rain. The implementation method is used so that the purpose of this service activity is to empower the community about managing household waste to be composted through composter, as well as training on composting from composter and biopori. The target of this activity is the mothers of family welfare coaching (PKK) in the village of Sedapurklagen, Benjeng Gresik. The result of this service is that the community has begun to process organic waste to make compost and million biopori pipes around the Posapur, Sedapurklagen Gresik to reduce the presence of standing water during the rainy season.